Factors Influencing the Teaching Practices of In-service Teachers in Inclusive Education: A Systematic Review - Miaomiao Wu; Dorothy DeWitt; Nor Nazrina Mohamad Nazry; Norlidah Alias; Yuliang Jiao (Universiti Sains Islam Malaysia, 2024)
Journal of Quran Sunnah Education & Special Needs, Volume 8 Issue 1 Page (76-90)